Flash pulmonary edema in a post arterial switch operation - High flow oxygen as a treatment modality - Kumar Jamuna; Hegde Rajesh; Maheshwari Sunita; Rao Shekar (Wolters Kluwer Medknow Publications, 2009)
We report a case of a 3-year-old boy who underwent an arterial switch operation with relief of left ventricular outflow tract obstruction and later presented with recurrent episodes of flash pulmonary edema. High-flow humidified oxygen with positive pressure support (Vapotherm) was used as a treatment modality, thereby avoiding intubation and mechanical ventilation.